Terapi Gangguan Mental menurut Perspektif Robert A. Emmons dan Syekh Ihsan Jampes: Sebuah Analisis Konsep dan Metode Penyembuhan: An Analysis of Concepts and Healing Methods - Arroisi, Jarman; Mahfud, Musthofa Ali (Journal of Sufism and Psychotherapy, 2025)
The increasing prevalence of mental disorders such as depression, anxiety, chronic stress, and post-traumatic stress disorder (PTSD) demands healing approaches that are not only clinically effective but also provide deeper spiritual meaning. Modern psychological interventions, such as cognitive behavioral therapy (CBT), mindfulness-based therapy, and gratitude interventions, have shown significant impact on improving mental health. However, these approaches are often considered limited due to their secular orientation and insufficient engagement with the transcendental dimension of human experience. This study aims to comparatively analyze the concept of gratitude as developed by Robert A. Emmons and the concept of syukur according to Syekh Ihsan Jampes, as well as to evaluate their potential integration within a holistic framework for mental disorder treatment. This research employs a qualitative approach through a literature study, drawing upon Emmons’ work (Thanks! How the New Science of Gratitude Can Make You Happier), Ihsan Jampes’ Sirāj al-Ṭālibīn, the Qur’an, Hadith, literature on positive psychology, and recent empirical studies. Content analysis and comparative methods were applied to examine the definitions, dimensions, similarities, and differences of the two concepts. The findings indicate that, first, gratitude and syukur both function as healing mechanisms by reducing stress, depression, and anxiety. Second, both enhance subjective well-being, sleep quality, prosocial behavior, and emotional resilience. Third, the main difference lies in their orientation: gratitude is rooted in an empirical-secular approach, while shukr is grounded in a theological-transcendental perspective. Fourth, their integration has the potential to create a comprehensive psycho-spiritual therapy that is clinically effective while also strengthening faith, morality, and meaning in contemporary life.